2017
DOI: 10.5603/fhc.a2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired expression of testicular androgen receptor and collagen fibers in the testis of diabetic rats under HAART: the role of Hypoxis hemerocallidea

Abstract: introduction. Wide spectrum of alterations associated with highly active antiretroviral therapy (HAART) has been reported. The current study aimed at evaluating the role of Hypoxis hemerocallidea (HH) aqueous extract on the testosterone levels, expression of androgen receptors and collagen fibers in the testes of streptozotocin--nicotinamide-induced diabetic rats under HAART regimen. Material and methods. Sixty two adult male Sprague-Dawley rats (189.0 ± 4.5 g) were divided into eight groups (8 animals in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
3
3
0
Order By: Relevance
“…This result agrees with the previous finding that documented abnormal morphology of seminiferous tubules marked with distorted epithelium in diabetic rats ( Ricci et al., 2009 ). Moreover, Ismail et al. (2017) reported an increase in collagen fibres with several distortions in diabetic rats, augmenting this present study's findings ( Ismail et al., 2017 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result agrees with the previous finding that documented abnormal morphology of seminiferous tubules marked with distorted epithelium in diabetic rats ( Ricci et al., 2009 ). Moreover, Ismail et al. (2017) reported an increase in collagen fibres with several distortions in diabetic rats, augmenting this present study's findings ( Ismail et al., 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, Ismail et al. (2017) reported an increase in collagen fibres with several distortions in diabetic rats, augmenting this present study's findings ( Ismail et al., 2017 ). It is worthy to note that the administration of HAART-AgNP in diabetic rats improved the testicular histological architecture that was marked with tubular atrophy and interstitial distension.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have reported the toxicity of many substances including plant extracts on the collagen fiber deposits in diabetic testis (Ismail et al, 2017), hypertensive epididymis (Mazen and Zidan, 2017), hepatic stellate cell distribution (Nishimura et al, 2012;Towne et al, 2015), and chronic kidney disease patients (Allon et al, 2019). As demonstrated in this recent study, the intensity of collagen fibers present in testis, caudal epididymis, liver, and renal tissues stained by Masson's trichrome, shows no difference between the control and DSF treatment groups.…”
Section: Discussionsupporting
confidence: 50%
“…Our laboratory has utilized various animal models to demonstrate potential interactions of plant-based adjuvants in many therapeutic conditions for diabetes (Ismail et al, 2017), hypertension (Azu, 2015), and alcohol-induced antiretroviral toxicity (Ogedengbe et al, 2018), exploring various markers for biochemical, immunological, and histomorphometric studies. The aim of this study was to evaluate and report the histopathological and biochemical effects of CcAgNPs in male Sprague-Dawley rats after multiple oral administrations.…”
Section: Introductionmentioning
confidence: 99%